Imagined and Actual Acupuncture Effects on Chronic Low Back Pain: A Preliminary Study - Jin Cao; Scott P. Orr; Georgia Wilson; Jian Kong (Neural Plasticity)
Background. Research suggests that imagined experiences can produce brain responses similar to those produced by actual experiences. Shared brain responses that support both imagination and perception may underlie the functional nature of mental imagery. In a previous study, we combined acupuncture and imagery to develop a new treatment method, video-guided acupuncture imagery treatment (VGAIT). We found that VGAIT significantly increased pain thresholds in healthy subjects. The aim of this study is to extend our previous finding by investigating whether VGAIT can relieve symptoms in patients with chronic low back pain. Methods. We first performed a single-arm study in which we administered video-guided acupuncture imagery treatment (VGAIT) on patients with chronic low back pain (cLBP) (Study 1, n=18, 12 females). We then compared our findings to those from a recently published study in which real or sham acupuncture treatment was applied on patients with cLBP (Study 2, n=50, 31 females) using a similar protocol. All patients in Studies 1 and 2 received 6 treatments over 4 weeks. Results. All three treatments (VGAIT, real, and sham acupuncture) significantly reduced pain severity as measured by a low back pain bothersomeness score. VGAIT produced similar effects to real acupuncture (p=0.97) and nonsignificantly greater pain bothersomeness relief compared to sham acupuncture (p=0.14). Additional analysis showed that there was no significant difference on the sensations evoked by different treatment modalities. Conclusion. These findings support VGAIT as a promising method for pain management.